Preserving fertility: using cyclophosphamide and other cytotoxics in young people. Issue 2 (13th September 2019) - Ledingham, David; Plant, Michael; Mustafa, Fayez; Patil, Bhimanagouda
Abstract : Cytotoxic agents such as cyclophosphamide are infrequently used in neurological practice. When they are, it is commonly in critically ill patients or in those with refractory inflammatory disorders. Cyclophosphamide in particular has a well-recognised negative impact on both female and male long-term fertility. This article summarises the data with regards the impact of cytotoxics on long-term fertility and describes the current options to preserve fertility in these patients. We hope this will provide neurologists with a useful aid for counselling patients for whom they are considering these treatments.